Development in The Analytical Gas Chromatography of Metal Dialkydithiophospate Complexes - DR PHILIP J MARRIOT (ASEAN Journal on Science and Technology for Development, 1986)
The gas chromotographic analysis of metal-containing compounds has been a small but reasonably active field for about 25 yeras. Analyses cover such as organometalics, metal complexes, and compounds such as hydrides and halides. Reviews of the fiels may be seen in the books by Moshier and Sievers (1), Guichon and Pommier (2) and Crompton (3), as well as the papers by Uden and Henderson (4) abd Rodrigues-Vasquez (5).